Calculation Method to Determine the Group Composition of Vacuum Distillate with High Content of Saturated Hydrocarbons; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Shafran T. Tatyana; Belinskaya N. S. Natalia Sergeevna (2016, 2016)
Title screen